Single-component epoxy adhesive for magnetic core bonding

By using components such as epoxy resin and siliconic anhydride curing agent with rigid connected link structures in magnetic core adhesion, the traditional magnetic core adhesion in terms of bonding thickness control and heat resistance is solved. Realize high -precision, low -linear thermal expansion coefficient and excellent humidity resistance performance, and improve production efficiency and product reliability.

CN119371920AActive Publication Date: 2025-01-28CHENGDU TALY TECH CO LTD

Patent Information

Application Number
CN202411655168.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Traditional magnetic core adhesives have shortcomings in controlling the accuracy and consistency of bonding thickness, and are difficult to achieve automated control and have low production efficiency. At the same time, after curing, traditional adhesives have a high linear thermal expansion coefficient and a large curing shrinkage rate, which affects the precise control of the inductance and may cause cracks or fractures of the core material.

Method used

The combination of epoxy resin with rigid linked ring structures and organic silicon -molicized acid anhydride curing agent is combined with liquid acid anhydride curing agent and glass microfin as interval particles, forming a low viscosity, high adhesive, and low -line -inflated expansion coefficient A single component epoxy adhesive with a low -curing volume contraction.

Benefits of technology

Realize the high accuracy and consistency of the thickness of the adhesion, reduce the complexity and processing difficulty of the production process, improve the consistency of the amount of inductance, and have excellent humidity and heat and heat resistance. Internal stress has improved product reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141947250000021
    Figure BDA0005141947250000021
  • Figure BDA0005141947250000041
    Figure BDA0005141947250000041
  • Figure BDA0005141947250000111
    Figure BDA0005141947250000111
Patent Text Reader

Abstract

The invention discloses a single-component epoxy adhesive for magnetic core bonding, which comprises A) an epoxy resin prepolymer containing a rigid linked ring structure and accounting for 30-60wt% of the weight percentages of A-D; b) an organic silicon modified anhydride curing agent which accounts for 15-40wt% of all the weight percentages of A-D; c) a liquid anhydride curing agent accounting for 15-42wt% of the weight percentages of A-D; d) a curing accelerator accounting for 0.5-5 wt% of all the weight percentages of A-D; and E) glass beads accounting for 5-30 wt% of the weight percentages of the components A-D. The adhesive disclosed by the invention has the characteristics of high adhesion, good heat resistance, low linear thermal expansion coefficient, low curing volume shrinkage rate, excellent humidity and heat resistance and excellent thermal shock resistance, and an adhesive layer with high thickness uniformity can be formed between magnetic cores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a single-component epoxy adhesive for bonding magnetic cores. Background Art

[0002] The magnetic core refers to a sintered magnetic metal oxide composed of a mixture of various iron oxides. It is a key part of electronic components and is widely used in transformers, inductors and electromagnetic components. In order to facilitate assembly, except for toroidal products, the magnetic cores of transformers and inductors are generally composed of two parts, such as the common PQ type, EE type, EI type, ER type, EP type, etc. During assembly, the two parts of the magnetic core are bonded together to form a reliable magnetic circuit structure, maintain the stability of the inductance, and prevent the magnetic core from vibrating and generating noise under the action of the magnetic field.

[0003] The core bonding has precise requirements for the relative position, matching gap, and adhesive layer thickness of the upper and lower cores after they are firmly bonded. The traditional production process generally uses a non-Newtonian fluid single-component epoxy adhesive with high viscosity and slow flow rate. After the glue is applied, the inductance is adjusted to the target value by longitudinal pressure regulation and transverse reciprocating shearing motion of the upper and lower cores. In the field of electronics and electrical appliances, the demand for miniaturization and integration is getting higher and higher, and the requirements for the accuracy and consistency of controlling the bonding thickness of the adhesive are higher. The traditional production process has poor control accuracy and consistency of the bonding thickness, and it is difficult to achieve automated control, resulting in low production efficiency.

[0004] The core adhesive also requires high bonding strength after curing, low linear thermal expansion coefficient, impact resistance, vibration resistance, low water absorption, moisture and water resistance, heat and humidity resistance, and small shrinkage during curing. After curing, it can maintain the original state, and the difference in inductance before and after curing is small. In addition, if the linear thermal expansion coefficient (CTE) and elastic modulus between the adhesive material and the core material do not match, a large internal stress will be generated under hot and cold shock conditions. When the internal stress is too large and exceeds the strength of the core material, it will cause the core material to crack or even break and fail, resulting in unqualified electrical performance of the product, which seriously affects the reliability of the product. Traditional core adhesives often reduce the thermal expansion coefficient of the adhesive by increasing the crosslinking degree of the adhesive (such as the nano-scale single-component tough epoxy composite for core bonding and its preparation method disclosed in patent document CN201711014852.6), but the crosslinking degree of the adhesive increases, and the curing shrinkage rate also increases accordingly, which makes the inductance difference of the transformer or inductor before and after curing large, which is not conducive to the precise control of the inductance. Summary of the invention

[0005] The present invention provides an epoxy resin adhesive for bonding magnetic cores, which has high adhesion, low linear thermal expansion coefficient, low curing volume shrinkage and excellent moisture and heat resistance. The epoxy adhesive has low viscosity and contains spacer particles for controlling the bonding gap. The control accuracy and consistency of the bonding thickness are good, which is very conducive to automatic control.

[0006] The present invention provides a one-component epoxy adhesive for bonding magnetic cores, comprising the following components:

[0007] A) Epoxy resin containing rigid linked ring structure;

[0008] B) an organosilicon-modified anhydride curing agent having the following structure (I):

[0009]

[0010] wherein R1 to R4 are each independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, and n represents an integer of 10 to 200 repeating units;

[0011] C) a liquid anhydride curing agent, wherein the liquid anhydride curing agent is liquid at room temperature and contains only one anhydride functional group in its molecular structure, wherein the room temperature refers to 25° C.;

[0012] D) curing accelerator;

[0013] E) glass microspheres, wherein the coefficient of variation of the average particle size of the glass microspheres should be less than 5%, and the amount of the glass microspheres added is 5 to 30 wt %, accounting for all weight percentages of A to D;

[0014] F) other additives, the addition amount of any of the other additives is 0-0.2wt%, accounting for all weight percentages of A-D.

[0015] The following is a detailed introduction to each component:

[0016] 1) Component A: Epoxy resin containing rigid linked ring structure

[0017] The epoxy resin containing a rigid linked ring structure is an epoxy resin prepolymer containing a rigid linked ring structure and having two epoxy functional groups at the ends of the molecular chain.

[0018] The epoxy resin containing the rigid linked ring structure can be selected from a combination of one or more of a naphthalene-type epoxy resin, a fluorene-type epoxy resin, and a dicyclopentadiene phenol epoxy resin. These epoxy resins contain a rigid linked ring aromatic structure and have the characteristics of high heat resistance, low water absorption, low linear thermal expansion coefficient, and low shrinkage. After being cured, these epoxy resins containing the rigid ring structure have ultra-low water absorption, low linear thermal expansion coefficient, and low cured volume shrinkage.

[0019] The naphthalene-type epoxy resin can be selected from any one or more of HP-4032, HP-4701, HP-4700, and HP-4770 of Nippon Ink and Chemicals Co., Ltd., or can be selected from any one or two of NC-7300L and NC-7000L of Nippon Kayaku Co., Ltd.

[0020] The fluorene epoxy resin can be selected from any one or more of EX-1010, EX-1020, EX-1030, EX-1040 and EX-1050 manufactured by Nagase Chemical Technology Co., Ltd.

[0021] The dicyclopentadiene phenol epoxy resin can be selected from any one or more of SQDN-301, SQDN-302, and SQDN-303 of Jinan Shengquan Group.

[0022] The epoxy resin containing the rigid linked ring structure preferably has a softening point below 80° C., and more preferably has a softening point below 60° C. The single-component epoxy adhesive for bonding magnetic cores prepared using these epoxy resins with low softening points has lower viscosity and is easier to construct.

[0023] The added amount of the epoxy resin containing the rigid linked ring structure is 30-60wt%, accounting for all weight percentages of A-D.

[0024] 2) Component B: an organosilicon-modified anhydride curing agent having the following structure (I)

[0025]

[0026] wherein R1 to R4 are each independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, and n represents an integer of 10 to 200 repeating units.

[0027] In formula (I), R 1 to R 4 , which may be the same or different, are monovalent hydrocarbon groups of 1 to 10 carbon atoms, preferably monovalent hydrocarbon groups of 1 to 6 carbon atoms, such as straight chain, branched chain or cyclic alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, tert-butyl and cyclohexyl, straight chain, branched chain or cyclic alkenyl groups such as vinyl, allyl, propenyl, butenyl, hexenyl and cyclohexenyl, aryl groups such as phenyl and tolyl, and aralkyl groups such as benzyl and phenethyl. These groups may be included in any desired ratio.

[0028] The subscript n in structure (I) represents the number of repeating units, and n is an integer from 10 to 200. If n is less than the minimum value in this range, the toughness is insufficient and the shear strength after thermal shock aging is insufficient; if n is greater than the maximum value in this range, the viscosity of the organosilicon-modified acid anhydride curing agent is too high to be used, and the linear thermal expansion coefficient of the cured epoxy resin is greatly affected.

[0029] The added amount of the organosilicon modified acid anhydride curing agent is 15-40wt%, accounting for all weight percentages of A-D.

[0030] 3) Component C: Liquid anhydride curing agent

[0031] Liquid anhydride curing agent is an anhydride that is liquid at room temperature. Liquid anhydride can reduce the viscosity of the adhesive system.

[0032] The liquid anhydride curing agent can be selected from one or more of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, and dodecenylsuccinic anhydride. The molecular structure of these liquid anhydride curing agents contains only one anhydride functional group.

[0033] The anhydride curing agent contains one anhydride functional group in its molecular structure, and the degree of crosslinking after curing is 2. The curing shrinkage rate of the adhesive using this anhydride curing agent is smaller than that of the adhesive using an anhydride curing agent containing two or more anhydride functional groups.

[0034] The amount of the liquid anhydride curing agent added is 15-42wt%, accounting for all weight percentages of A-D. If the amount of the liquid anhydride curing agent added is less than the minimum value of this range, the viscosity of the one-component epoxy adhesive for magnetic core bonding will be too high, which is not conducive to construction; if the amount of the liquid anhydride curing agent added is greater than the maximum value of this range, the viscosity of the one-component epoxy adhesive for magnetic core bonding will be too low, the fluidity will be too good, and it will be easy to sag.

[0035] 4) Component D: Curing accelerator

[0036] The curing accelerator is selected from imidazole compounds known in the art, boron trifluoride-amine adducts, microcapsule-coated latent amine curing agents, etc. Suitable imidazole compounds include, but are not limited to, 2-methyl-4-ethylimidazole (2E4MZ), 2-phenylimidazole (2PZ), 2-methylimidazole (2MZ) and 1-benzyl-2-phenylimidazole (1B2PZ). Suitable microcapsule-coated latent amine curing agents include HX-3722, HX-3742, HX-3921HP, HX-3922HP, etc. from Asahi Chemical.

[0037] The added amount of the curing accelerator is 0.5-5wt%, accounting for all weight percentages of A-D.

[0038] 5) Component E: Glass beads

[0039] Glass microbeads are used as spacer particles for controlling the bonding gap. The shape of the glass microbeads can be elliptical, drop-shaped or spherical. The glass microbeads preferably have a smooth surface. The glass microbeads are preferably solid glass beads, especially solid glass balls. The glass material used is not subject to any special restrictions as long as it is compatible with the adhesive.

[0040] The average diameter of the glass microspheres is 10 to 150 μm, and the coefficient of variation of the average diameter should be less than 5%. The shape of the glass microspheres is preferably spherical. For non-spherical microspheres, the diameters refer to the maximum measurable diameter of the glass microspheres.

[0041] The amount of glass beads added is 5 to 30 wt%, accounting for all weight percentages of A to D. If the amount of glass beads added is too little, the spacing effect cannot be fully exerted, making the magnetic core bonding gap uneven. If the amount of glass beads added is too much, the contact area between the single-component epoxy adhesive used for magnetic core bonding and the magnetic core bonding surface becomes smaller, which will affect the bonding strength.

[0042] If the glass beads difference coefficient is greater than 5%, the bonding gap of the magnetic core will become uneven, which is not conducive to the automated bonding of the magnetic core.

[0043] 6) Component F: other additives

[0044] Optionally, the one-component epoxy adhesive for bonding the magnetic core may also include other additives, such as a leveling agent, a defoaming agent, a wetting and dispersing agent, etc. The amount of any additive added is 0-0.2 wt %, accounting for all weight percentages of A-D.

[0045] The leveling agent is preferably one of BYK-333, BYK-307, BYK-378, BYK-310 or BYK-354 produced by BYK Chemical.

[0046] The defoamer is preferably one of BYK-066N, BYK-055, BYK-A535, BYK-054, BYK-088, BYK-1796 or BYK-1790 produced by BYK Chemical.

[0047] The wetting and dispersing agent is preferably one of BYK-W094, BYK-111 or BYK2700 produced by BYK Chemical.

[0048] The content of each component of the one-component epoxy adhesive for bonding a magnetic core of the present invention can be selected within the above-mentioned range. An optional component content is as follows:

[0049] A one-component epoxy adhesive for bonding magnetic cores, comprising the following components:

[0050] A) an epoxy resin prepolymer containing a rigid linked ring structure, accounting for 40 to 50 wt% of all weight percentages of A to D;

[0051] B) an organosilicon-modified acid anhydride curing agent having the above structure (I), accounting for 15 to 20 wt % of all weight percentages of A to D;

[0052] C) a liquid anhydride curing agent, accounting for 19 to 42 wt % of all weight percentages of A to D;

[0053] D) a curing accelerator, accounting for 1.5 to 2.0 wt% of all weight percentages of A to D;

[0054] E) Glass microspheres, accounting for 7-25 wt % of all weight percentages of A-D.

[0055] The present invention uses an epoxy resin containing a rigid linked ring structure and an anhydride curing agent to form the main components of the adhesive system. Compared with other curing agents, the anhydride curing agent has a small curing volume shrinkage, strong rigidity after curing, high heat deformation temperature, good heat resistance, low linear thermal expansion coefficient, and excellent mechanical and electrical properties; but since the anhydride contains an ester bond after curing, it is easily corroded by alkali and has water absorption, and it cannot be used as a curing agent for epoxy resin adhesives for magnetic core bonding in the usual sense. The present invention uses an epoxy resin containing a rigid linked ring structure to solve this problem. Since the rigid linked ring structure is a mesh chain arrangement, the free volume is reduced, the linear thermal expansion coefficient and water absorption are reduced, thereby protecting the ester bond after the anhydride is cured to a certain extent, inhibiting the hydrolysis of the ester group, and the rigidity of the rigid linked ring structure further reduces the curing volume shrinkage rate. In addition, the present invention uses a bifunctional rigid linked ring structure epoxy resin and a bifunctional anhydride curing agent. Compared with conventional epoxy resin adhesives that improve heat resistance and reduce linear thermal expansion coefficient by increasing the crosslinking degree, the adhesive of the present invention has a low crosslinking degree after curing and a smaller curing volume shrinkage rate. This makes the single-component epoxy adhesive for magnetic core bonding of the present invention have good heat resistance, low linear thermal expansion coefficient, and small curing volume shrinkage, overcoming the disadvantages of conventional epoxy adhesives that reduce the linear thermal expansion coefficient and improve heat resistance by increasing the degree of cross-linking, but cannot take into account the curing volume shrinkage.

[0056] The present invention adopts an organic silicon modified acid anhydride curing agent. The acid anhydride in the molecule is very rigid after curing, which is effective for improving the heat resistance, mechanical strength and electrical properties of the cured epoxy resin composition. The siloxane chain contained in the molecule is effective for reducing the elasticity of the cured epoxy resin composition to form a flexible elastomer. The introduction of the long-chain organic silicon segment reduces the elastic modulus and reduces the internal stress. Controlling and reducing the internal stress caused by the bonding material is of great significance for improving the reliability and long-term stability of transformers and inductors.

[0057] At the same time, silicone has a hydrophobic structure. Using silicone segments to toughen epoxy resin is also beneficial to improving the hydrophobicity of epoxy resin, thereby having a certain protective effect on the ester group and further inhibiting the hydrolysis of the ester group.

[0058] The organosilicon-modified anhydride curing agent uses a long-chain organosilicon segment to connect two anhydride groups. Due to the high flexibility of the long-chain organosilicon segment, the effective cross-linking degree of the anhydride is not increased. Therefore, the organosilicon-modified anhydride curing agent has little effect on the curing volume shrinkage.

[0059] The present invention combines a liquid anhydride curing agent with an organosilicon-modified anhydride curing agent to reduce the viscosity of the system. In addition, glass microbeads with a fixed thickness are added as spacer particles, and the longitudinal pressure and transverse shear force required in the bonding process of the upper and lower magnetic cores are significantly reduced, the processing difficulty is significantly reduced, and the consistency of inductance is significantly improved. In the bonding process of the magnetic cores, the adhesive between the spacer particles and the bonding surface can be fully excluded, so that the bonding gap of the magnetic cores is more accurate and more uniform, and it is not easy to have a situation where one side is high and the other side is low.

[0060] Compared with the prior art, the present invention has at least the following beneficial effects:

[0061] 1. The single-component epoxy adhesive for core bonding has the characteristics of high adhesion, good heat resistance, low linear thermal expansion coefficient, low curing volume shrinkage, excellent moisture and heat resistance and excellent thermal shock resistance. Through formula design, it takes into account both low linear thermal expansion coefficient and low curing volume shrinkage, so that the difference in inductance before and after curing of the transformer or inductor is small, which is conducive to precise control of inductance, and the inductance changes little with temperature.

[0062] 2. The single-component epoxy adhesive used for core bonding has low viscosity and is easy to construct. In addition, glass beads with a fixed thickness are added as spacer particles. The longitudinal pressure and lateral shear force required in the bonding process of the upper and lower cores are significantly reduced, the processing difficulty is significantly reduced, the thickness of the bonding layer is highly uniform, and the consistency of inductance is significantly improved. In the process of core bonding, the adhesive between the spacer particles and the bonding surface can be fully removed, making the core bonding gap more precise and uniform, and easy to realize automatic control, thereby improving production efficiency. DETAILED DESCRIPTION

[0063] Preparation of organosilicon modified anhydride curing agent:

[0064] Synthesis Example 1

[0065] Synthesis of trimellitic anhydride chloride: 288g trimellitic anhydride, 150g benzene, 232g thionyl chloride are added to a flask equipped with a condensing device, a stirring device and a tail gas absorption device in order. The flask is placed in a water bath, the stirring device is turned on, 0.96g of catalyst dimethyl diamide is added to the flask at 10-15°C, and 119g of pyridine is added at the same time. The dripping is completed in about 30 minutes, and then the water bath is turned on for heating, and the reaction liquid is reacted at reflux temperature for about 5 hours. It is observed that the solid matter gradually dissolves, and the reaction liquid changes from turbid to clear, accompanied by smoke and bubbles. Finally, the precipitate in the bottle is completely dissolved to form a light yellow clear liquid, and smoke and bubbles are no longer generated. Benzene and excess thionyl chloride are distilled out at normal pressure, and a small amount of the front fraction is distilled out by reduced pressure distillation. The middle fraction is collected, and the collected liquid is cooled to obtain white crystalline trimellitic anhydride chloride, which is sealed and stored.

[0066] Synthesis Example 2

[0067] Synthesis of hydroxyalkyl silicone oil 1: In a 2L four-necked flask equipped with a stirring and condensing device, 800g of dimethylsiloxane oligomer with Si-H groups at both ends (molecular formula is shown in the following structure (II), number average molecular weight 800, equivalent to n=10) was added, 0.01g of chloroplatinic acid was preheated to 80°C, and nitrogen was passed to deoxygenate for 15 minutes, and then 265.5g of ethylene glycol monoallyl ether was added dropwise to the flask. After the addition, the mixture was aged at 100°C for 2 hours, and the excess ethylene glycol monoallyl ether was removed under reduced pressure to obtain hydroxyalkyl silicone oil 1.

[0068] Synthesis Example 3

[0069] Synthesis of hydroxyalkyl silicone oil 2: 1170 g of dimethylsiloxane oligomer with Si-H groups at both ends (molecular formula is shown in the following structure (II), number average molecular weight 1170, equivalent to n=15) was added to a 2L four-necked flask equipped with a stirring and condensing device, 0.014 g of chloroplatinic acid was preheated to 80°C, and nitrogen was passed to deoxygenate for 15 minutes, and then 265.5 g of ethylene glycol monoallyl ether was added dropwise to the flask. After the addition, the mixture was aged at 100°C for 2 hours, and the excess ethylene glycol monoallyl ether was removed under reduced pressure to obtain hydroxyalkyl silicone oil 2.

[0070] Synthesis Example 4

[0071] Synthesis of hydroxyalkyl silicone oil 3: 1880 g of dimethylsiloxane oligomer with Si-H groups at both ends (molecular formula is shown in the following structure (II), number average molecular weight is 3760, equivalent to n=50) was added to a 3L four-necked flask equipped with a stirring and condensing device, 0.02 g of chloroplatinic acid was preheated to 80°C, and nitrogen was passed to deoxygenate for 15 minutes, and then 132.8 g of ethylene glycol monoallyl ether was added dropwise to the flask. After the addition, the mixture was aged at 100°C for 2 hours, and the excess ethylene glycol monoallyl ether was removed under reduced pressure to obtain hydroxyalkyl silicone oil 3.

[0072] Synthesis Example 5

[0073] Synthesis of hydroxyalkyl silicone oil 4: 2232 g of dimethylsiloxane oligomer with Si-H groups at both ends (molecular formula is shown in the following structure (II), number average molecular weight 11160, equivalent to n=150) was added to a 3L four-necked flask equipped with a stirring and condensing device, 0.023 g of chloroplatinic acid was preheated to 80°C, and nitrogen was passed to deoxygenate for 15 minutes, and then 53.1 g of ethylene glycol monoallyl ether was added dropwise to the flask. After the addition, the mixture was aged at 100°C for 2 hours, and the excess ethylene glycol monoallyl ether was removed under reduced pressure to obtain hydroxyalkyl silicone oil 4.

[0074] Synthesis Example 6

[0075] Synthesis of hydroxyalkyl silicone oil 5: 2972 ​​g of dimethylsiloxane oligomer with Si-H groups at both ends (molecular formula is shown in the following structure (II), number average molecular weight 14860, equivalent to n=200) was added to a 5L four-necked flask equipped with a stirring and condensing device, 0.03 g of chloroplatinic acid was preheated to 80°C, and nitrogen was passed to deoxygenate for 15 minutes, and then 53.1 g of ethylene glycol monoallyl ether was added dropwise to the flask. After the addition, the mixture was aged at 100°C for 2 hours, and the excess ethylene glycol monoallyl ether was removed under reduced pressure to obtain hydroxyalkyl silicone oil 5.

[0076]

[0077] Synthesis Example 7

[0078] Synthesis of silicone modified trimellitic anhydride curing agent 1:

[0079] Add 210.57g of trimellitic anhydride chloride and solvent benzene into a flask equipped with a condensing device, a stirring device and a tail gas absorption device. Place the flask in a cold water bath, turn on the stirring device, and add 79.1g of pyridine to the flask at 0-10°C. It takes about 30 minutes to complete the addition. After the addition is completed, continue to stir and react for about 1 hour. At this time, a milky white precipitate is observed in the flask, and the mixed solution in the flask becomes turbid from clear.

[0080] After the reaction for 1 hour, 502 g of hydroxyalkyl silicone oil 1 was added dropwise, and then the heating was turned on. After reflux reaction for 3 hours, the reaction was stopped and filtered while hot to leave the liquid. The solvent benzene was then removed by rotary evaporation, and the remaining white viscous material was vacuum dried to obtain the silicone-modified trimellitic anhydride curing agent 1.

[0081] Synthesis Examples 8 to 11

[0082] Synthesis of silicone modified trimellitic anhydride curing agent 2-5:

[0083] According to the same method as in Synthesis Example 7, the hydroxyalkyl silicone oil was replaced with 687 g of hydroxyalkyl silicone oil 2 to obtain trimellitic anhydride curing agent 2;

[0084] According to the same method as in Synthesis Example 7, the hydroxyalkyl silicone oil was replaced with 1982 g of hydroxyalkyl silicone oil 3 to obtain trimellitic anhydride curing agent 3;

[0085] According to the same method as in Synthesis Example 7, the hydroxyalkyl silicone oil was replaced with 5682 g of hydroxyalkyl silicone oil 4 to obtain trimellitic anhydride curing agent 4;

[0086] According to the same method as in Synthesis Example 7, the hydroxyalkyl silicone oil was replaced with 7532 g of hydroxyalkyl silicone oil 5 to obtain trimellitic anhydride curing agent 5.

[0087] Examples and comparative examples of one-component epoxy adhesive for magnetic core bonding

[0088] Prepare the raw materials according to the raw materials and amounts in Table 1, and prepare the one-component epoxy adhesive for magnetic core bonding according to the following method:

[0089] Add epoxy resin prepolymer containing rigid linked ring structure, organosilicon modified acid anhydride curing agent, and liquid acid anhydride curing agent to the batching cylinder, stir and mix evenly with a high-speed disperser, transfer to a planetary stirring kettle, add glass beads and other additives, stir and mix evenly, cool to room temperature, add a curing accelerator, stir and mix for about 30 minutes, vacuum degassing, and packaging to obtain a single-component epoxy adhesive for magnetic core bonding. The comparative example preparation method is similar, and only the corresponding raw materials need to be used to replace the raw materials in the embodiment.

[0090] Table 1 Examples and Comparative Examples Raw material types and amounts (mass, parts)

[0091]

[0092]

[0093] (Continued) Table 1 Examples and Comparative Examples Types of Raw Materials and Amounts (mass, parts)

[0094]

[0095]

[0096] The adhesives obtained in each embodiment and comparative example were tested, and the test method was as follows:

[0097] 1) Curing conditions: 120-180°C, heating for 30-120 minutes.

[0098] 2) Water absorption test: Determine the water absorption in 23℃ water for 24h according to GB / T 1034.

[0099] 3) Shear strength test: Take an appropriate amount of sample, cure it according to the above curing conditions, and make Al-Al shear slices. Determine according to GB / T7124. Test the shear strength at 25℃ and 125℃ respectively.

[0100] 4) Glass transition temperature (Tg) test: Take an appropriate amount of sample, cure it according to the above curing conditions, and make a 3mm*25mm*10mm rubber strip. Use dynamic thermal mechanical analysis (DMA) to measure it at 5℃ / min and raise the temperature to 200℃.

[0101] 5) Linear thermal expansion coefficient test: Take an appropriate amount of sample, cure it according to the above curing conditions, and make a 3mm*5mm*5mm rubber block. Use thermomechanical analysis (TMA) to test, and heat it to 200℃ at 5℃ / min.

[0102] 7) Curing volume shrinkage test: Take an appropriate amount of sample and cure it according to the above curing conditions. Measure according to ISO 3521.

[0103] 8) Moisture and heat resistance evaluation:

[0104] According to GB / T 7124, 5 Al-Al shear pieces were prepared and aged in an oven at 85°C and 85% humidity for 1000 hours. After being taken out and restored to room temperature for 24 hours, the average shear strength was tested and compared with the shear strength of the shear piece placed at 25°C. The evaluation criteria are as follows:

[0105] Excellent: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.8 or more;

[0106] Good: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.7 to 0.8 (excluding 0.8);

[0107] Middle: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.6 to 0.7 (excluding 0.7);

[0108] Poor: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is less than 0.6;

[0109] 9) Thermal shock resistance evaluation:

[0110] According to GB / T 7124, 5 Al-Al shear pieces were prepared and aged in an oven at 85°C and 85% humidity for 1000 hours. After being taken out and restored to room temperature for 24 hours, the average shear strength was tested and compared with the shear strength of the shear piece placed at 25°C. The evaluation criteria are as follows:

[0111] Excellent: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.8 or more;

[0112] Good: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.7 to 0.8 (excluding 0.8);

[0113] Middle: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is 0.6 to 0.7 (excluding 0.7);

[0114] Poor: The ratio of the shear strength after aging to the shear strength of the shear piece placed at 25°C is less than 0.6;

[0115] 10) Thickness uniformity test of bonding layer:

[0116] Ten sheared pieces were prepared from a smooth aluminum sheet and cross-sectioned. Based on the cross-section image, the average thickness of the adhesive layer was measured. The uniformity of the thickness of the adhesive layer was determined based on the following criteria. The criteria for determining the uneven thickness of the adhesive layer were:

[0117] Excellent: the ratio of the minimum value of the thickness of the adhesive layer to the maximum value of the thickness of the adhesive layer (minimum value of the thickness of the adhesive layer / maximum value of the thickness of the adhesive layer) is 0.9 or more;

[0118] Good: The ratio of the minimum thickness of the adhesive layer to the maximum thickness of the adhesive layer (minimum thickness of the adhesive layer / maximum thickness of the adhesive layer) is 0.7 or more and less than 0.9;

[0119] Poor: The ratio of the minimum thickness of the adhesive layer to the maximum thickness of the adhesive layer (minimum thickness of the adhesive layer / maximum thickness of the adhesive layer) is less than 0.7.

[0120] Table 2 Test results of embodiments and comparative examples

[0121]

[0122] (Continued) Table 2 Example and Comparative Example Test Results

[0123]

[0124] 1. Examples 1-5 are single-component epoxy adhesives for magnetic core bonding with different repeating unit numbers n of the organosilicon-modified acid anhydride curing agent. From the test data in Table 2, it can be seen that with the increase of the repeating unit number n, the corresponding epoxy adhesive viscosity increases and the linear thermal expansion coefficient increases. This is because with the increase of the repeating unit number n, the molecular weight of the organosilicon-modified acid anhydride curing agent increases, and the length of the flexible organosilicon chain segment increases, and the corresponding viscosity increases. In addition, the closer the repeating unit number n is to the lower limit of 10 specified above, the lower the shear strength after thermal shock aging. This is because the length of the flexible organosilicon chain segment decreases, reducing the toughness of the epoxy adhesive. Within a certain range, Example 6 reduces the amount of glass microbeads, and Example 7 increases the amount of glass microbeads. Both examples have achieved good performance.

[0125] 2. Comparative Example 1 Compared with Example 3, the epoxy resin containing a rigid linked ring structure was replaced with a bisphenol A epoxy resin without a rigid linked ring structure. As a result, the water absorption rate increased significantly, and the moisture and heat resistance also decreased significantly. In addition, the bisphenol A epoxy resin has lower rigidity, so the glass transition temperature decreases and the heat resistance also decreases (the shear strength at 125°C decreases). Comparative Example 1 has too low viscosity and too high fluidity, so it is not conducive to sizing.

[0126] 3. Comparative Example 2 does not contain the organosilicon modified acid anhydride curing agent relative to Example 3, resulting in reduced toughness of the adhesive, which is manifested in reduced thermal shock resistance and reduced shear strength. Comparative Example 2 has too low viscosity and too high fluidity, so it is not conducive to sizing.

[0127] 4. Comparative Example 3 reduces the amount of liquid acid anhydride (methyltetrahydrophthalic anhydride) relative to Example 3 and is below the specified minimum value. As a result, the viscosity increases significantly and the thickness uniformity of the adhesive layer is poor.

[0128] 5. Comparative Example 4 increases the amount of liquid anhydride (methyltetrahydrophthalic anhydride) relative to Example 3, which is higher than the specified maximum value. As a result, the viscosity is too low and the fluidity is too high, which is not conducive to sizing. The water absorption rate is also increased.

[0129] 6. In Comparative Example 5, relative to Example 3, the coefficient of variation of the average diameter of the glass microspheres increases and exceeds the specified maximum value, resulting in a decrease in the uniformity of the thickness of the bonding layer.

[0130] 7. In Comparative Example 6, relative to Example 3, the amount of glass beads added was increased, exceeding the prescribed maximum value, resulting in a decrease in the uniformity of the thickness of the bonding layer.

[0131] 8. Comparative Example 7 Compared with Example 3, the amount of glass beads added is reduced and is lower than the specified minimum value, resulting in a decrease in the uniformity of the thickness of the bonding layer.

[0132] 9. Comparative Example 8 Compared with Example 3, multifunctional epoxy resin NPPN-638S (average functionality 3.6) was added, and the curing volume shrinkage rate increased significantly and the shear strength decreased. The present invention does not use multifunctional epoxy resin, and the crosslinking degree of multifunctional epoxy resin is too high, which will lead to high curing shrinkage rate.

[0133] 10. Comparative Example 9 Compared with Example 3, a multifunctional acid anhydride curing agent, pyromellitic dianhydride, was added. As a result, the curing shrinkage rate increased, the shear strength decreased, and the thickness uniformity of the adhesive layer decreased.

Claims

1. A one-component epoxy adhesive for bonding magnetic cores, characterized in that: Contains the following components: A) an epoxy resin containing a rigid linked ring structure, accounting for 30 to 60 wt % of all weight percentages of A to D; B) an organosilicon-modified anhydride curing agent having the following structure (I), accounting for 15 to 40 wt% of all weight percentages of A to D: wherein R1 to R4 are each independently a monovalent hydrocarbon group having 1 to 10 carbon atoms, and n represents an integer of 10 to 200 repeating units; C) a liquid anhydride curing agent, accounting for 15 to 42 wt % of all weight percentages of A to D; D) a curing accelerator, accounting for 0.5 to 5 wt% of the total weight percentage of A to D; E) Glass microspheres, accounting for 5-30 wt% of all weight percentages of A-D.

2. The one-component epoxy adhesive for bonding magnetic cores according to claim 1, characterized in that: The n is an integer from 10 to 50.

3. The one-component epoxy adhesive for bonding magnetic cores according to claim 1, characterized in that: The n is an integer from 50 to 200.

4. The one-component epoxy adhesive for bonding magnetic cores according to any one of claims 1 to 3, characterized in that: The epoxy resin containing a rigid linked ring structure is an epoxy resin prepolymer containing a rigid linked ring structure and having two epoxy functional groups at the ends of the molecular chain.

5. The one-component epoxy adhesive for bonding magnetic cores according to claim 4, characterized in that: The epoxy resin containing a rigid linked ring structure is selected from a combination of one or more of a naphthalene epoxy resin, a fluorene epoxy resin, and a dicyclopentadiene phenol epoxy resin; and the softening point of the epoxy resin containing a rigid linked ring structure is lower than 80°C.

6. The one-component epoxy adhesive for bonding magnetic cores according to claim 4, characterized in that: In the formula (I), R 1 to R 4 Same or different, R 1 to R 4 Selected from methyl, ethyl, propyl, isopropyl, n-butyl, cyclic alkyl, tert-butyl, cyclohexyl, vinyl, allyl, propenyl, butenyl, hexenyl, cyclohexenyl, phenyl, tolyl, benzyl, phenethyl.

7. The one-component epoxy adhesive for bonding magnetic cores according to claim 4, characterized in that: The liquid anhydride curing agent is selected from one or more of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, and dodecenylsuccinic anhydride.

8. The one-component epoxy adhesive for bonding magnetic cores according to claim 7, characterized in that: The curing accelerator is selected from imidazole compounds, boron trifluoride-amine adducts, and microcapsule-coated latent amine curing agents. The imidazole compounds are selected from any one of 2-methyl-4-ethylimidazole, 2-phenylimidazole, 2-methylimidazole, and 1-benzyl-2-phenylimidazole. The microcapsule-coated latent amine curing agent is selected from any one of HX-3722, HX-3742, HX-3921HP, and HX-3922HP.

9. The one-component epoxy adhesive for bonding magnetic cores according to claim 4, characterized in that: The average diameter of the glass microspheres is 10-150 μm, and the average diameter variation coefficient is less than 5%.

10. The one-component epoxy adhesive for bonding magnetic cores according to claim 4, characterized in that: The one-component epoxy adhesive for bonding the magnetic core further comprises a leveling agent, a defoaming agent or a wetting and dispersing agent, and the added amount of the leveling agent, the defoaming agent or the wetting and dispersing agent is 0-0.2wt%, accounting for all weight percentages of A-D.

Citation Information

Patent Citations

  • Nanoscale single-component tough epoxy composite for magnetic core bonding and its preparation method

    CN107652933B

  • Preparation method of trimellitic anhydride chloride

    CN103626729A

  • Fuel cell bipolar plate waterway sealing bonding adhesive and preparation method thereof

    CN116426234A

  • Silicone-modified acid anhydride and its production

    JP1993339279A

  • Epoxy resin composition

    JP1994157723A

Cited By

  • A single-component epoxy adhesive for magnetic core bonding, a preparation method and application thereof

    CN122668683A